Design of Optimal LLCL Filter with an Improved Control Strategy for Single Phase Grid Connected PV Inverter - K. Arulkumar; D. Vijayakumar; K. Palanisamy (Institute of Advanced Engineering and Science, 2018)
The third order LLCL filter is gaining more attractive in grid connected PV inverter in terms of material cost saving than LCL filter. Several active and passive damping techniques prevail in mitigating the resonance problem for maintaining the grid power quality standards. In this paper an improved passive damping is examined with reduction of power loss for the LLCL filter. Particularly, it reduces the switching ripple much better than LCL filter, with a decrease in volume of the inductance. The filter design is also developed for the operation of stiff grid. Mathematical operations and transfer function are derived with frequency response for the accuracy of the filter design. In addition, comparative analysis of passive and improved passive damping control is proposed. The control strategy is improved with feedback linearization in order to avoid the glitches in inverter control and is verified with prototype grid connected PV inverter.